2018
DOI: 10.1186/s12931-018-0821-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased telomere length in the small airway epithelium suggests accelerated aging in the lungs of persons living with human immunodeficiency virus (HIV)

Abstract: Human immunodeficiency virus (HIV) infection is associated with an increased risk of chronic obstructive pulmonary disease (COPD) independent of cigarette smoke exposure. Previous studies have demonstrated that decreased peripheral leukocyte telomere length is associated with HIV, suggesting an accelerated aging phenomenon. We demonstrate that this process of telomere shortening also occurs in the lungs, with significant decreases in telomere length observed in small airway epithelial cells collected during br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Furthermore, PLWH have significantly shorter telomeres in small airway bronchial epithelial cells compared with HIV-negative individuals, controlling for smoking, age, and sex (308). Postulated mechanisms of these senescent changes include HIVdriven increases in small airway epithelial cell turnover or alterations in the telomere length in the basal stem cells that give rise to the small airway epithelium (308). These studies provide intriguing data on the role of senescence in HIVassociated COPD.…”
Section: Copdmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, PLWH have significantly shorter telomeres in small airway bronchial epithelial cells compared with HIV-negative individuals, controlling for smoking, age, and sex (308). Postulated mechanisms of these senescent changes include HIVdriven increases in small airway epithelial cell turnover or alterations in the telomere length in the basal stem cells that give rise to the small airway epithelium (308). These studies provide intriguing data on the role of senescence in HIVassociated COPD.…”
Section: Copdmentioning
confidence: 88%
“…HIV-related proteins can also cause significant alveolar epithelial barrier dysfunction, associated with changes in tight junctions (167). PLWH have shorter telomere lengths in airway epithelial cells compared with HIVnegative controls, suggestive of accelerated aging within the small airway epithelium, even after adjusting for age (308).…”
Section: Airway Epitheliummentioning
confidence: 99%
See 1 more Smart Citation
“…3 Decreased peripheral leukocyte telomere length has long been associated with HIV. 4 HIV infection has also been connected with an increased risk of chronic obstructive pulmonary disease independent of cigarette smoke exposure. 3 It has detected that telomere shortening also occurs in the lungs, with significant decreases in telomere length observed in small airway epithelial cells.…”
Section: Immune Checkpoint Inhibitors In Hiv-positive Patients With Nmentioning
confidence: 99%
“…3 It has detected that telomere shortening also occurs in the lungs, with significant decreases in telomere length observed in small airway epithelial cells. 4 It has been evidenced that HIV-1-specific CD8þT cells from HIV-1 controllers are characterized by long telomeres and high levels of constitutive telomerase activity, whereas HIV-1-specific CD8þT cells from HIV-1 progressors show telomere shortening with limited telomerase activity. 5 It has been suggested that telomere shortening plays a causal role in the functional deficiency of HIV-1-specific CD8þT cells in chronic progressive infection.…”
Section: Immune Checkpoint Inhibitors In Hiv-positive Patients With Nmentioning
confidence: 99%